TRANSFORMASI SOSIAL EKOMNOMI MASYARAKAT DESA PANDES ATAS PERAN KOMUNITAS PEDULI SUNGAI UJUNG HILIR (KPSUH) - Niko Darmawan; Bambang Santosa (Journal of Development and Social Change, 2020)
Komunitas Peduli Sungai Ujung Hilir (KPSUH) is a river community located in Pandes Village, Klaten Regency with its background was formed because it considers the environment in the region.The research aims to understand how the role of the community in transforming the socio-economy community, understanding the supporting and inhibiting factors, as well as the benefits and thoughts of the community. The subject in this qualitative study is Komunitas Peduli Sungai Ujung Hilir using the functional structural of the Talcott Parsons. Sampling is naturalistic inquiry with observations, interviews and documentation. Data validity with source triangulation. KPSUH has a work program in completing the program named Pandawa. The purpose of the community is to reduce the waste that has become an old problem, to restore and restore the function of the river to restore in propely. In this study, the communities that participated in the transformation that occurred in the Ujung Hilir River area both in terms of ecology and society. KPSUH received support from both the community and the village administration of Pandes. The barriers needed by the community are the time required and considerable energy in the process of chane, factors from outside of Pandes area and misinformation. The benefit of this community role is the transformation in the socio-economic field received by residents who can now utilize the river area for positive activities.